Low prevalence of antibodies against SARS‐CoV‐2 among voluntary blood donors in Guangzhou, China. Issue 3 (30th September 2020) - Xu, Ru; Huang, Jieting; Duan, Chaohui; Liao, Qiao; Shan, Zhengang; Wang, Min; Rong, Xia; Li, Chengyao; Fu, Yongshui; Wang, Hao
Abstract: Since the first case of COVID‐19 reported in late December of 2019 in Wuhan, China, the SARS‐CoV‐2 virus has caused approximately 20 million infections and 732 thousand deaths around the world by 11 August 2020. Although the pathogen generally infects the respiratory system, whether it is present in the bloodstream and whether it poses a threat to the blood supply during the period of the outbreak is of serious public concern. In this study, we used enzyme‐linked immunosorbent assay (ELISA) to screen total antibodies against SARS‐CoV‐2 in 2199 blood donors, who had donated blood at the Guangzhou Blood Center during the epidemic. The Ig‐reactive samples were further characterized for IgA, IgG, and IgM subtypes by ELISA and viral nucleic acid by real‐time polymerase chain reaction. Among the 2199 plasma samples, seven were reactive under total antibodies' screening. Further testing revealed that none of them had detectable viral nucleic acid or IgM antibody, but two samples contained IgA and IgG. The IgG antibody titers of both positive samples were 1:16 and 1:4, respectively. Our results indicated a low prevalence of past SARS‐CoV‐2 infection in our blood donors, as none of the tests were positive for viral nucleic acid and only 2 out of 2199 (0.09%) of samples were positive for IgG and IgA. There would be a limited necessity for the implementation of such testing in blood screening in a COVID‐19 low‐risk area. Highlights: The prevalence of past SARS‐CoV‐2 infection was relatively low among voluntary blood donors in Guangzhou, China Screening of SARS‐CoV‐2 among voluntary blood donors may not be in priority in Guangzhou, China, because of the low risk of transmission via transfusion.